Reformulating Criminal Law Policy on Child Perpetrators of Human Trafficking in Indonesia: A Child Victim-Offender Approach - Alendra Alendra; Said Rizal; Roswita Sitompul; Tommy Leonard; Nurul Hidayat Ab Rahman (IJCLS (Indonesian Journal of Criminal Law Studies), 2026)
This study analyzes criminal law policy and the reformulation of regulations concerning children as perpetrators of prostitution in human trafficking in Indonesia. Current laws, notably the Anti-Trafficking in Persons Law and the Juvenile Criminal Justice System Law, create a normative and practical dilemma: the Anti-Trafficking in Persons Law focuses on retributive punishment, while the Juvenile Criminal Justice System Law emphasizes child protection, diversion, and rehabilitation. However, existing studies have not sufficiently addressed the legal ambiguity of children simultaneously acting as perpetrators and victims in trafficking cases. This divergence generates ambiguity in determining the legal status of child offenders, resulting in inconsistent enforcement and potential injustice. Using a normative juridical approach, the study proposes the Child Victim Offender concept, recognizing that children may act as both perpetrators and victims based on their participation, coercion, and socio-psychological circumstances. Recommendations include harmonizing the Anti-Trafficking in Persons Law and the Juvenile Criminal Justice System Law, clarifying definitions, establishing criteria for child culpability, and applying limited retributive sanctions integrated with rehabilitative guidance and social reintegration. This approach balances law enforcement with child protection, strengthens justice for victims, and supports responsive, child-centered criminal law reform aligned with national and international obligations.